Derivation of Glaze from Cathode Ray Tubes (CRTs) for Ceramic Wares - AJADI, Michael Olaniyi; KALILU, Razaq Olatunde Rom (ABUAD Journal of Engineering and Applied Sciences, 2024)
Introduction of digital display makes cathode ray tube to be largely obsolete. The tube with its screen becomes waste at the end of the products lifecycle. This study, which combined laboratory experimentation and studio practices, aimed at production of glass glaze with cathode ray tube screen. Cathode ray tubes of four different colours were used for the study. The tubes were washed, pulverized and sieved according to their colour, elementally analysed using Particle Induce X-ray Emission, and milled into two batches per colour with first batch mixed with ball clay and second batch mixed with ball clay and additive chemical material of borax. The glaze batches were applied on eight bisque-fired tiles and fired at 1100 0C. The glazes yielded greenish grey, greyish purple, transparent grey and dark grey. This is significance towards the diversification of Nigeria’s economy for solving solid waste disposal challenges for a better and safe environment. The study has proven that cathode ray tubes with addition of borax and ball clay are suitable for glaze production and provided elemental information to guide the glaze formulation.